PENGARUH PENGGUNAAN METODE DEMONSTRASI TERHADAP HASIL BELAJAR FISIKA SISWAPADA MATERI POKOK GELOMBANG BUNYI KELAS XII DI SMA NEGERI BATANG ONANG - Siregar, Dedes Asriani (Program Studi Pendidikan Fisika, Institut Pendidikan Tapanuli Selatan, 2022)
This study aims to find out wether there is influence of demonstration methodto students’ achievement in sound wave of the XII students’ of SMA Negeri 1.Batang Onang this research was done by using descriptive and inferential analysis.The population is all of XII students of SMA Negeri 1. Batang Onang. Consist of 2 classes, it is70 student. Sampling technique by using random sampling, it is 32 students.The mean test for demonstration method is 3.1, it is good category. The mean of to students’achievement in sound wave of the XII students of SMA Negeri 1. Batang Onang is76, it is good category.Based on the calculation in inferential analysis, it is found that t count is 4.946 and if it is compared to t table in 95% significant, it is found 1.70. After comparing t cound and t table, it is got that t count is greater than t table (4.946>1.70)The hypothesis is accepted. Means that there is significant influence of demonstration method to students’ achievement in sound wave of the XII students of SMA Negeri 1 Batang Onang